Institutionalized Corruption and the Kleptocratic State - Harm, Christian (IMF Working Papers; Working Paper ;, 1999)
This paper argues that corruption patterns are endogenous to political structures. Thus, corruption can be systemic and planned rather than decentralized and coincidental. In an economic system without law or property rights, a kleptocratic state may arise as a predatory hierarchy from a state of pure anarchy. A dictator minimizes the probability of a palace revolution by creating a system of patronage and loyalty through corrupt bureaucracy. Competitive corruption patterns are associated with anarchy and weak dictators, while strong dictators implement a system of monopolistic corruption. Efforts at public sector reform may meet resistance in countries featuring such systemic corruption.